A revision of Autolytinae (Syllidae, Polychaeta) with special reference to Scandinavian species, and with notes on external and internal morphology, reproduction and ecology. - Gidholm, Lennart (Arkiv för Zoologi. Series 2, 1966)
This paper describes two new species and redescribes seven old ones. It reports a number of synonyms and gives new definitions for Autolytus Grube and Proceraea Ehlers. The descriptions, obtained from a large material of living specimens, present data showing the variability of the characters. In some general chapters attention is devoted to unicellular epidermal glands, parapodial glands, refractive granules in the intestine, a characteristic alternation pattern in the cirri, structure of the tube, stolonization, etc. The taxonomic usefulness of the characters, both old and new, is discussed. Earlier confusion in autolytine taxonomy appears to be partly due to wrong evaluations of important criteria. The bifid appendages of the polybostrichus are demonstrated to be epitokous lateral antennae. PaIps are lacking in all true stolons. The autolytine genera belong to one of two well-defined groups, one containing Autolytus and Myrianida, and the other containing Proceraea, Procerastea, and Virchowia. Fundamental characters are the presence or absence of segmental ciliation, the type of parapodial gland and stolonization, and the shape of the bayonet setae. In Autolytus edwarsi, in particular, samples of individuals taken within the same geographical area may differ notably. It is concluded that subspecific distinctions can only be made in the light of very extensive knowledge of the populations. Eleven species of Autolytinae have been obtained in Scandinavian waters.
World Polychaeta Database (WPolyDb). Publication date: "Tryckt den 23 november 1966"